Ternstroemia gymnanthera Cleyera, Japanese Ternstroemia - Edward Gilman (EDIS, 2007)
This document provides an overview of Ternstroemia gymnanthera, commonly known as Japanese ternstroemia or cleyera. It describes the plant’s characteristics, including its dense, dark green foliage that changes color with the seasons, and its small, fragrant white flowers that give way to red fruits. The plant is noted for its moderate growth rate, upright habit, and tolerance to various soil types and light conditions. It is recommended for use as a screen, hedge, or specimen plant due to its ornamental features and low maintenance requirements. The document also covers the plant’s propagation methods, pest resistance, and cultural needs, emphasizing its suitability for year-round planting in USDA hardiness zones 7 through 10. Original publication date October 1999.